African Union and its institutions - Akokpari, John, 1957-; Ndinga-Muvumba, Angela; Murithi, Timothy (Auckland Park, South Africa : Fanele ; [Cape Town] : Centre for Conflict Resolution, 2008)
Written by eminent scholars on Africa and practitioners who have worked in or with the African Union (AU), this report brings together the analysis and research of 17 largely Pan-African scholars, policymakers, practitioners, and civil society representatives. A particularly timely and welcome addition to the pioneering literature about this young and potentially powerful institution, this analysis presents a positive but realistic picture of the AU while diagnosing several key challenges, including Africa's security and governance problems.
Pt. 1. From the OAU to the AU : conceptual issues -- pt. 2. Peace and security -- pt. 3. Governance and civil society -- pt. 4. The Diaspora and external actors.
Includes bibliographical references and index.
Keywords: African Union; African Union; Pan-Africanism.; African cooperation; National security -- Africa; International law; Political Science/ World / General; Africa -- Politics and government -- 21st century